Analysis of IoT services, data platforms and re-use of data and solutions in a Smart city context - Jan Markendahl (International Telecommunications Society (ITS), 2022)
In this paper deployment and operation of IoT services are analysed in a smart city context. A multitude of similar IoT solutions, networks, platforms that often appear as separate closed stovepipes within the same organisation. This often means that it is difficult to re-use systems, knowledge of usage and experiences from procurements within city administrations or within the city. The same obstacles exist when to re-use solutions between cities Municipalities in Sweden to large extent agree on the need to use interoperable IoT solutions and to avoid stovepipe within the city. However, many new solutions are "closed" and specific for the own unit, and still new stovepipe solutions are deployed. In this paper we look into the reasons why the stovepipes (still) exist. Results and findings are presented in the following areas Stove pipes are still around - It is not so common with one central IoT platform in the municipality - Issues with data sharing - Scalability in the technical domain - Scalability in the business domain.
Keywords: 330